The emergence of frailty and sarcopaenia in diabetes mellitus: description of inter-relationships and clinical importance. Issue 2 (June 2016) - Sinclair, Alan J.; Sinclair, Harriet; Bellary, Sri; Rodriguez-Manas, Leocadio
Abstract : Diabetes mellitus is a highly prevalent chronic disease, with an associated heavy personal and public health burden of disability, morbidity and mortality. The focus of care for older patients with diabetes is prevention of functional decline, with early intervention rather than attempting to recover function later. Diabetes doubles the risk of frailty. An important contributor towards physical frailty is sarcopaenia, which manifests as an age-related loss of skeletal muscle volume and power. Frailty is not an inevitable consequence of the ageing process; it is a dynamic and potentially reversible condition that highlights the importance of early recognition and intervention. In this review, we examine the evidence for linking diabetes to frailty and sarcopaenia and how the emergence of these conditions should lead to changes in clinician behaviour in terms of assessment of function and goal setting. High-quality, focused research in this area is now mandatory.